EXPLORING THE QUALITY AND STRUCTURE OF THESIS STATEMENTS IN DIPLOMA STUDENTS’ ARGUMENTATIVE WRITING - Amat, Rafidah; Mansor, Nur Syazwanie; Abu Hassan, Nor Asni Syahriza; Badri, Zawani; Abd Rahim, Mas Aida; Brian, Muhammad Shyazzwan Ibrahim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Academic Writing is an important skill for tertiary students at higher education. One of the components of academic writing is thesis statement which it established the writer’s stance and direction for the essay. However, students are still struggling with writing a good thesis statement or at least a structurally sound. Thus, this study aims to examine the structure and the quality written by Part 3 diploma students in Universiti Teknologi MARA Kedah Branch. There were 26 thesis statements collected form students; written argumentative essay which was a part of their Final Assessment. The thesis statements were analysed based on their quality and their structural patterns. Findings revealed that students relied heavily on the same formulaic stance markers such as “I strongly believe…” and often used simple cause-effect formula. A minority showed the use of generalised sentence structures but most of the students demonstrated the ability to use a higher argumentative potential. In the perspective of quality, the students mostly categorised as medium – high range quality. Hence, these results showed that students relied on memorised structures and have limited linguistics styles when constructing thesis statement. It is essential to enhance students’ awareness on thesis statement structures in improving their academic writing skills.